PENGARUH PUPUK ANORGANIK DAN PUPUK KANDANG DIPERKAYA NP-ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG PULUT (Zea mays ceratina L.) - Shadana Krishnamurti; Yafizham Yafizham; ADRIANI Darmawati; Dwi Retno Lukiwati (BUANA SAINS, 2021)
Fertilization is one of the factors that influence the growth and production of sticky maize. This study examined the effect of organic-NP enriched manure on the growth and yield of sticky maize. The study used a Randomized Complete Block Design (RCBD) with four replicates. The treatments are P0 (ZA + TSP), P1 (cow manure + ZA + TSP), P2 (goat manure + ZA + TSP), P3 (poultry manure+ ZA + TSP), P4 (cow manure + Gliricidia sepium + BP), P5 (goat manure + Gliricidia sepium + BP), P6 (poultry manure + Gliricidia sepium + BP). The parameters observed were plant height, number of leaves, chlorophyll content, cobs length, and cobs diameter. The results showed that the number of leaves, chlorophyll content in the generative phase, and cobs diameter in treatment P1 (cow manure + ZA + TSP) is equivalent to P4 (cow manure + Gliricidia sepium + BP), P2 (goat manure + ZA + TSP) is equivalent to P5 (goat manure + Gliricidia sepium + BP), and P3 (poultry manure+ ZA + TSP) is equivalent to P6 (poultry manure + Gliricidia sepium + BP). The cobs length in treatment P3 is significantly higher compared to P6. All treatments have no effect on plant height and chlorophyll content in the vegetative phase.